Surfactant layers at the air/water interface: structure and composition. - Lu, JR; Thomas, R; Penfold, J (Elsevier, 2000)
The use of neutron reflectometry to study the structure and composition of surfactant layers adsorbed at the air/water interface is reviewed. A critical assessment of the results from this new technique is made by comparing them with the information available from all other techniques capable of investigating this interface.